Adult Granulosa Cell Tumours of the Ovary Seven Case Reports - Faten LIMAIEM; Saloua MEJRI; Imen KHELIL; Ahlem LAHMAR; Saadia BOURAOUI; Sabeh MZABI-REGAYA (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2015)
Background:Ovarian granulosa cell tumours are low-grade malignant sex cord-stromal tumours. They represent 2 to 3% of all ovarian cancers and occur mainly within the adult population. Aim:  to provide an updated overview on ovarian adult granulosa cell tumours.Patients Methods:in our retrospective study, we reviewed seven cases of adult granulosa cell tumours that were diagnosed at the pathology department of Mongi Slim hospital over a fourteen-year period (2002- 2015). Clinical and pathRIiological characteristics were retrospectively analyzed. Results: The patients of our series ranged in age between 39 and 64 years (mean = 53 years). The  most  common  presenting  symptom  was  abnormal  uterine  bleeding  (n=5)  followed  by  pelvic pain  (n=4).  All  patients  underwent  surgical  treatment  including  total  hysterectomy  with  bilateral salpingo-oophorectomy  (n=4),  hysterectomy  with  right  salpingo-oophorectomy  (n=1)  and  salpingo-oophorectomy (n=2). Histopathological examination of the surgical specimen confirmed the diagnosis of adult granulosa cell tumour in all cases. Conclusions:Adult granulosa cell tumours of the ovary are considered as low grade malignancies with  a  relatively  more  favourable  prognosis  compared  with  much  more  commonly  encountered epithelial  ovarian tumours. A  prolonged  post-therapeutic  follow-up  is  necessary  because  of  the  risk of recurrences.